New Adenosine Derivatives from Aizoon canariense L.: In Vitro Anticholinesterase, Antimicrobial, and Cytotoxic Evaluation of Its Extracts - Bakr, Riham O.; El-Behairy, Mohammed F.; Elissawy, Ahmed M.; Elimam, Hanan; Fayed, Marwa A. A. (Molecules (Basel, Switzerland), 2021)
Aizoaceae is a large succulent family characterized by many psychoactive species. Aizoon canariense L., a wild neglected plant traditionally used in gastrointestinal ailments, has been the subject of a limited number of phytochemical and biological studies. Therefore, herein, we investigated the in vitro cytotoxic, antimicrobial, and anticholinesteraseactivity of the aerial parts of A. canariense L. and analyzed the phytochemical compositions of the lipoidal and alkaloidal fractions. Petroleum ether extract showed the presence of behenic and tricosylic acid, while an in-depth investigation of the alkaloidal fraction revealed the identification of new adenine based alkaloids (1–5), which were isolated and identified for the first time from Aizoon canariense L. Their structures were elucidated based on extensive spectroscopic analyses. The alkaloidal extract showed a powerful cytotoxic effect (IC50 14–28 μg/mL), with the best effect against colon carcinoma, followed by liver and breast carcinomas. The alkaloidal extract also had a potent effect against Candida albicans and Escherichia coli, with minimum inhibitory concentrations (MIC) values of 312.5 and 625 µg/mL. The in vitro anticholinesterase activity was potent, with IC50 < 200 ng/mL for the tested extracts compared with 27.29 ± 0.49 ng/mL for tacrine.